PENGARUH KOMUNIKASI TERAPEUTIK TERHADAP TINGKAT KECEMASAN IBU HAMIL TRIMESTER III DI KLINIK BERSALIN CIBRO HJ.LASMA KEC.KISARAN KAB.ASAHAN TAHUN 2020 - Tetty Junita Purba (Jurnal Kajian Kesehatan Masyarakat, 2022)
Therapeutic communication is an interpersonal relationship between officers health and the client in this relationship both get shared experiences in order to improve the client's emotional experience. number Infant mortality (IMR), one of which is the mother's emotional condition during pregnancy until birth. Anxiety (anxiety) is a disorder with feelings that characterized by feelings of deep fear or worry and sustainable. The period of pregnancy, childbirth and post-natal is a period of the occurrence of great stress, anxiety, emotional disturbances and adjustment. This study aims to determine and identify the level of decrease in maternal anxiety in the face of normal delivery by type gender, age, education and occupation.This study uses a quasi-experimental design with Design One Group Pretest and Posttest without groups control. The population in this study were 34 respondents. In this research using non-random (non-probability) sampling with the technique of Purposive Sampling. Of the 34 respondents studied, the majority of respondents were in the good category, namely as many as 18 respondents (52.9%), and the majority of respondents in the sufficient category, namely as many as 8 respondents (23.5%), and the majority of respondents in the less category 8 were 8 people (23.5%). Results of this statistical test using the Wilcoxon sign rank test in get p-value 0.001 < 0.05. Then Ha is rejected.